2021
DOI: 10.3389/fonc.2021.754835
|View full text |Cite
|
Sign up to set email alerts
|

ADORA2A-AS1 Restricts Hepatocellular Carcinoma Progression via Binding HuR and Repressing FSCN1/AKT Axis

Abstract: BackgroundHepatocellular carcinoma (HCC) is one of the most aggressive malignancies. Increasing evidence revealed that long noncoding RNAs (lncRNAs) were frequently involved in various malignancies. Here, we explored the clinical significances, roles, and mechanisms of lncRNA ADORA2A antisense RNA 1 (ADORA2A-AS1) in HCC.MethodsThe clinical significances of ADORA2A-AS1 in HCC were analyzed using RNA sequencing (RNA-seq) data from The Cancer Genome Atlas (TCGA) project. The expressions of ADORA2A-AS1, Fascin Act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…Cells were fixed with 4% paraformaldehyde in phosphate-buffered saline for 30 min. Cell nuclei were subsequently stained with 4ʹ,6-diamidino-2ʹ-phenylindole and then observed with a fluorescence microscope (Leica, Nikon, Olympus, Zeiss) [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cells were fixed with 4% paraformaldehyde in phosphate-buffered saline for 30 min. Cell nuclei were subsequently stained with 4ʹ,6-diamidino-2ʹ-phenylindole and then observed with a fluorescence microscope (Leica, Nikon, Olympus, Zeiss) [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Among these genes, some have been reported to play an important part in HCC, but some have not been studied deeply. For example, Pu et al found that FSCN1 restricted HCC progression after receiving upstream inhibition (40). Liu et al found that FSCN1 overexpression promoted the migration and invasion of HCC cells (41).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Pu et al. found that FSCN1 restricted HCC progression after receiving upstream inhibition ( 40 ). Liu et al.…”
Section: Discussionmentioning
confidence: 99%
“…ADORA2A-AS1 (adenosine A2A receptor) bound HuR and thus prevented its binding to FSCN1 (fascin actin-bundling protein 1) transcripts, which decreased FSCN1 transcript stability and repressed AKT pathway activation. Low levels of ADORA2A-AS1 were correlated with poor prognosis in hepatocellular carcinoma (Pu et al, 2021).…”
Section: Mrna Stabilitymentioning
confidence: 93%